Challenges of democratization in Kurdistan region of Iraq and the role of the elite 2003-2018 - Mahmood, Rezhwan Tahir (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This thesis deals with the process of democratization in Iraqi Kurdistan. It aims to critically study the key problems faced by the Kurds throughout the transition of power since the establishment of a new constitution in Iraq in 2005. At the same time, it refers to the efforts of the political leaders and political parties in taking this sequence in establishing a historical and political entity for the Kurds. This research tries to utilize publications of some famous scholars such as Robert Dahl and Terry Lynn Karl to describe the theories of democracy. Similarly, the theories are used to assess the primary background in order to critically analyze the field of Iraqi Kurdistan’s politics and governance. This thesis similarly integrated the significance of the elite and political parties in defining their commitment towards the Kurdistan Region. The findings of this study indicate that the main issues output such as pointing out the main challenges facing the process and providing solutions for them. This can contribute to changes in democracy throughout the region of Iraqi Kurdistan. Similarly, this thesis exposes the important political events which describe the current situation in the region. This qualitative study employs interviews using purposive sampling as a method to collect data regarding the role of elites and the obstacles faced by the democratization process in Iraqi Kurdistan.